Pengaruh Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan - Deddy Junaedi (Fakultas Ekonomi Universitas Panca Marga, 2016)
This study uses qualitative research methods with an explanatory approach. Source of data derived from primary data and secondary data. The analysis technique used is the technique of multiple linear regression analysis.From the test results is known that two independent variables work discipline and give effect to the variable compensation tied to the performance of employees amounted, which means that the independent variable discipline and compensation work together or simultaneously significant effect on the dependent variable employee performance in Institutions of Brilliant Education Centre Probolinggo and the remaininginfluenced by other variables outside two independent variables studied. Thus the first hypothesis in this proven research. From the results of multiple linear regression equation, the effect of independent variables work discipline and compensation with employee performance dependent variable on Institutions of Brilliant Education Centre Probolinggo there was a strong and significant influence. Keywords: discipline, compensation and employee performance